Synthesis of 5-Oxo-2-Arylamino Thiazol-[4,5-d]-Pyrans - RAJPUT, A.P. (Asian Journal of Chemistry, 2010)
Initially (E)-5-(4-oxo-2-arylamino thiazolyl) acrylic acids (3a-f) were prepared from 4-oxo-2-arylamino thiazole-5-carboxaldebydes (2a-f) using Perkin's reaction. The acrylic acids (3a-f) on heating with polyphosphoric acid (PPA) at 245°C formed intermediates (4a-f) (not isolated) which on hydrolysis with cold alkali yielded pyrans, (5a-f). The structures of acrylic acids and pyrans were confirmed by physical as well as chemical methods.